Alendronic Acid as Ionic Liquid: New Perspective on Osteosarcoma - Teixeira, Sónia (2022)
Herein the quantitative synthesis of eight new mono- and dianionic Organic Salts and Ionic Liquids (OSILs) from alendronic acid (ALN) is reported by following two distinct sustainable and straightforward methodologies, according to the type of cation. The prepared ALN-OSILs were characterized by spectroscopic techniques and their solubility in water and biological fluids was determined. An evaluation of the toxicity towards human healthy cells and also human breast, lung and bone (osteosarcoma) cell lines was performed. Globally, it was observed that the monoanionic OSILs showed lower toxicity than the corresponding dianionic structures to all cell types. The highest cytotoxic effect was observed in OSILs containing a [C2OHMIM] cation, in particular [C2OHMIM][ALN]. The latter showed an improvement in IC50 values of ca. three orders of magnitude for the lung and bone cancer cell lines as well as fibroblasts in comparison with ALN. The development of OSILs with high cytotoxicity effect towards the tested cancer cell types, and containing an anti-resorbing molecule such as ALN may represent a promising strategy for the development of new pharmacological tools to be used in those pathological conditions.